Carboxymethyl Dextran-Based Nanomicelle Coatings on Microarc Oxidized Titanium Surface for Percutaneous Implants: Drug Release, Antibacterial Properties, and Biocompatibility. (12th July 2022) - Ye, Weiliang; Zhou, Minghao; Zhang, Luxuan; Yu, Jingwei; Fan, Junjun; Wei, Hongbo
Abstract : Bacterial contamination and biofilm formation onpercutaneous implants can lead to device failure and be life-threatening. To solve this issue, we constructed a carboxymethyl dextran- (CMD-) based nanomicelle antibacterial coating on the microarc-oxidized titanium (MAO-Ti) surface (described in the supplementary file). The self-assembled CMD-based nanomicelles and octadecylamine (ODA) were developed as a drug carrier and loaded with minocycline (MC). The characterization and stability of the MC-loaded nanomicelles were determined. The surface roughness, hydrophilicity, and drug release property of the coatings were also investigated. Our findings showed that the cross-linked MC-loaded nanomicelles (MC@(ODA-CMD)CL ) were more stable than the uncross-linked nanomicelles. Moreover, MC@(ODA-CMD)CL was successfully incorporated into the pores of MAO-Ti, which significantly increased the surface hydrophilicity of the coatings without influencing their surface roughness. In addition, the coatings demonstrated a sustained release time of 360 h, with a cumulative release rate reaching 86.6%. Staphylococcus aureus (S. aureus) was used to determine the antibacterial properties of the coatings, and human skin fibroblasts were seeded on them to investigate their biocompatibility. The results showed that the coatings significantly reduced the number of adhesive S. aureus and promoted the viability, adhesion, and morphology of the human skin fibroblasts compared to smooth titanium (S-Ti) sheets. In conclusion, MC-loaded CMD-based nanomicelles coated on MAO-Ti surface (MC@(ODA-CMD)CL -Ti) demonstrated sustained-release properties, excellent antibacterial properties and biocompatibility, and promising potential as coatings for percutaneous implants.